PHENOMENA OF JAPAN'S POPULAR CULTURE HEGEMONY IN INDONESIA: ITS RELEVANCE IN STRENGTHENING NATIONAL CULTURE KOENTJARANINGRAT PERSPECTIVE - Revi Dicky Adistu; Sartini Sartini; Kusuma Putri (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2023)
The development of Japanese popular culture is spreading worldwide, especially in Indonesia. Indonesia has a diversity of local wisdom values and national culture that is rich in culture with noble traditions and artistic values that are now starting to erode Japanese popular foreign culture. The research findings explain that there are people in a community, especially the Yogyakarta, Jakarta and Bandung areas, who are eroded by Japanese culture by demonstrating that fashion and language are products of Japanese popular culture, which has implications for the loss of inherent national identity as national identity. In this case, Koentjaraningrat's cultural philosophy from the perspective of the seven cultural elements answers how to prevent a developed nation from being eroded by westernization from Western (Japanese) influences without eliminating local wisdom and cultural values by strengthening national culture.Keyword: Popular culture1, national culture2, modernzation3